TYPES AND FUNCTIONS OF SYNTACTICAL STYLISTIC DEVICES: ELLIPSIS, INVERSION, RHETORICAL QUESTION, REPETITION (Scientific Conference on Multidisciplinary Studies, 2025)
This is complete about types and function of syntactical stylistic devices: ellipsis, inversion, rhetorical question and repetition.